Development of pressure ulcers on the face in patients undergoing non-invasive ventilation - Ribas, Patrícia (2016)
Background The use of Non-Invasive Ventilation (NIV) has been increasing in clinical practice, however, the evidence has shown that its implementation may lead to development of ulcers of the face. Objective: to determine the prevalence of face ulcers on the face of patients admitted in an Intermediate Care Unit (ICU) submitted to NIV and to identify the factors associated to its development. Methods A prospective study conducted in a ICU between September and December 2015. Inclusion criteria of: age ≥ 18 years, patients admitted to the ICU, submitted to NIV and without ulcers of the face at the time of admission, lead us to a sample of 30 participants. Data were collected through a questionnaire, the Braden and Glasgow scale.The prevalence of ulcers on the face was of 26.7 % with a mean onset time of 3.3 ± 1.1 days. Participants were mostly males (70 %), with a mean age of 74.2 ± 10.3 years. Those who have developed an ulcer showed an older average age of 76.5 years, 16.7 % were changing sensitivity, 16.7 % had the facial skin intact and dry, 26.7 % used reused masks and 16.7 % had an ulcer Grade II. There was a statistically significant positive correlation between the development of an ulcer with the number of hours of daily NIV, the number of days of NIV, days of hospitalization, and a negative correlation with the level of consciousness. Conclusions We observed a high prevalence of ulcers. Thus, this emphasizes the need for further research to increase knowledge to subsidize ulcer prevention interventions in patients with NIV.